Engineered Cyanobacteria‐Hydrogel Microecological System for Oxygen Reprogramming Synergizes Immunomodulation With Anabolism in Osteoarthritis Therapy - Lerong Yang; Chong Shen; Hongjun Huang; Siyi Liu; Zeyu Huang; Licheng Xi; Huan Cao; Li Zheng; Zainen Qin (Advanced Science, 2026)
ABSTRACT Osteoarthritis remains a major clinical challenge due to its complex pathophysiology involving chronic inflammation and progressive cartilage degradation. Current treatments largely fail to address the dual demands of synovial anti‐inflammation and cartilage anabolism, particularly under the critical yet often overlooked influence of oxygen zonation within articular tissues. In this study, we propose a novel microorganism oxygen metabolism engineering strategy using an injectable cyanobacteria‐laden hydrogel (R‐alga) that enables light‐dependent dynamic oxygen regulation to mimic native physiological oxygen gradients. Under infrared ray (red) light irradiation, cyanobacteria within R‐alga efficiently produce oxygen via photosynthesis, specifically targeting and alleviating hypoxia in the inflamed synovial region. This process significantly suppresses the aberrant expression of HIF‐1α in macrophages, ameliorates their metabolic dysfunction, and effectively scavenges ROS, ultimately inducing macrophage polarization toward an pro‐regenerative phenotype. In the absence of light, cyanobacteria within R‐alga actively consume oxygen through respiration, creating and maintaining a physiologically relevant hypoxic microenvironment in the cartilage defect area. This environment stabilizes HIF‐1α expression in chondrocytes, activates the HIF‐1α‐DOT1L signaling axis, and significantly enhances the biosynthesis of key cartilage matrix components, thereby facilitating cartilage repair. Collectively, the microorganism oxygen metabolismengineering strategy offers a breakthrough for precise control of the osteoarthritis microenvironment and therapy.